2021
DOI: 10.1093/mnras/stab2408
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of equal-mass binary near-Earth asteroid 2017 YE5: a possible dormant Jupiter-family comet

Abstract: Photometric observations of the nearly equal-mass binary near-Earth asteroid 2017 YE5 were carried out at the Observatório Astronômico do Sertão de Itaparica (OASI, Brazil) and at the Blue Mountains Observatory (BMO, Australia) between July and August 2018, shortly after it made a close approach to Earth in June 2018. These observations allowed to determine an orbital period of the system in good agreement with the result of the radar observations. Our results also indicate that the 2017 YE5 system is not full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The difference in the SC/OC ratios is within the uncertainty limits: 0.32 ± 0.02 (α) and 0.30 ± 0.02 (β). Monteiro et al (2021) reported a very low geometric albedo of 0.03, which is consistent with an effective diameter of ∼1200 m, or two components with sizes of ∼900 m and ∼800 m, when H = 19.2. This low albedo and its heliocentric orbit with a high eccentricity of 0.71 have led to the suggestion that 2017 YE5 may be a dormant Jupiter-family comet that exhibits a D-type spectrum (Monteiro et al 2021).…”
Section: Ye5mentioning
confidence: 60%
See 1 more Smart Citation
“…The difference in the SC/OC ratios is within the uncertainty limits: 0.32 ± 0.02 (α) and 0.30 ± 0.02 (β). Monteiro et al (2021) reported a very low geometric albedo of 0.03, which is consistent with an effective diameter of ∼1200 m, or two components with sizes of ∼900 m and ∼800 m, when H = 19.2. This low albedo and its heliocentric orbit with a high eccentricity of 0.71 have led to the suggestion that 2017 YE5 may be a dormant Jupiter-family comet that exhibits a D-type spectrum (Monteiro et al 2021).…”
Section: Ye5mentioning
confidence: 60%
“…Monteiro et al (2021) reported a very low geometric albedo of 0.03, which is consistent with an effective diameter of ∼1200 m, or two components with sizes of ∼900 m and ∼800 m, when H = 19.2. This low albedo and its heliocentric orbit with a high eccentricity of 0.71 have led to the suggestion that 2017 YE5 may be a dormant Jupiter-family comet that exhibits a D-type spectrum (Monteiro et al 2021). This classification would place 2017 YE5 as one of the only D-type NEAs observed using radar, if not the only one.…”
Section: Ye5mentioning
confidence: 60%
“…Recent studies estimate that nearly 15% of NEOs larger than 200 m should be binaries (Margot et al 2015). Up to now, we know of the existence of at least 50 multiple systems (Margot et al 2015;Monteiro et al 2021), and even two triple NEOs (Brozović et al 2011;Becker et al 2015). Radar has proven to be a powerful method of detecting binary NEOs, enabling the discovery of secondary NEOs in 72% of the cases, while photometric measurements have been used to detect the remaining 28%.…”
Section: Introductionmentioning
confidence: 99%
“…There are many known binary asteroids with a larger mass central asteroid and a smaller mass satellite asteroid [10], but only four known near-Earth binary asteroids with nearly equal mass, with 2017 YE 5 being the fourth discovered. The other three known near-Earth binary asteroids with nearly equal mass are (69230) Hermes, (190166) 2005 UP 156 , and 1994 CJ 1 [15]. In the main asteroid belt there are two more binary asteroids with nearly equal mass, and these are 90 Antiope and (300163) 2006 VW 139 [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the main asteroid belt there are two more binary asteroids with nearly equal mass, and these are 90 Antiope and (300163) 2006 VW 139 [10]. Of these six binary asteroids with nearly equal mass, (300163) 2006 VW 163 is also classified as a comet with designation 288P [10], and 2017 YE 5 is also considered a possible dormant Jupiter-family comet [15].…”
Section: Introductionmentioning
confidence: 99%